2021
DOI: 10.1088/1755-1315/678/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Granulated activated carbon production based on petroleum coke

Abstract: The current tendency of the world oil refining towards a decrease in the fuel oil production and raise petroleum refinery efficiency is expressed in a significant increase of the delayed coking units capacity. This approach leads to an increase in the production of low-quality sulphurous petroleum coke, which is difficult to use for the production of electrodes, which makes it necessary to search for new ways of using this product. Present study considers the production possibility of granulated activated carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The findings indicated that a standard carbonization temperature of 700 • C and subsequent activation in a water vapor environment at 800 • C are required for pet coke. These ideal thermal treatment conditions can be considered a standard for producing granulated AC [99]. Heat treatment was also carried out to obtain oxygen-rich AC using pet coke as a starting material.…”
Section: Preparation Of Carbon Materialsmentioning
confidence: 99%
“…The findings indicated that a standard carbonization temperature of 700 • C and subsequent activation in a water vapor environment at 800 • C are required for pet coke. These ideal thermal treatment conditions can be considered a standard for producing granulated AC [99]. Heat treatment was also carried out to obtain oxygen-rich AC using pet coke as a starting material.…”
Section: Preparation Of Carbon Materialsmentioning
confidence: 99%
“…Нефтяные коксы, как правило, содержат более 99 мас. % углерода, что позволяет рассматривать их как перспективное альтернативное сырьё для получения дроблённых активированных углей [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionunclassified